Determining the Hazards Analysis of Nickel-Rich Lithium-Ion Battery Thermal Runaway under Different States of Charge - Jiang, Kun; Gu, Pingwei; Huang, Peng; Zhang, Ying; Duan, Bin; Zhang, Chenghui (Novel Perspectives of Engineering Research Vol. 5, 2022)
In this paper, the nickel-rich 18650 lithium-ion batteries with the Li[Ni0.8Co0.1Mn0.1]O2 cathode in different SOC conditions are taken to investigate the TR characteristics using the extended volume plus acceleration calorimeter (EV+-ARC). The lithium-ion battery industry has been developing rapidly, with energy density and capacity constantly improving. However, the ensuing safety accidents of lithium-ion power batteries have seriously threatened the personal safety of passengers. Therefore, more and more attention has been paid to the thermal safety research of lithium-ion batteries, such as thermal runaway (TR) mechanism analysis and prevention methods, etc. In this paper, the nickel-rich 18650 lithium- ion batteries with Li[Ni0.8Co0.1Mn0.1]O2 cathode in different states of charge (SOC) are taken to investigate the TR characteristics using an extended volume plus acceleration calorimeter (EV+-ARC). In order to evaluate the TR characteristics, some characteristic parameters such as battery voltage, surface temperature, temperature rise rate, etc. are selected from the experiment to analyze the influence of SOC on the critical state of TR. It can be seen from the experiment results that the maximum temperature of the battery surface decreases with the decrease of SOC, while the self- generated heat temperature and TR trigger temperature increases with the decrease of SOC.